Regional labour market dynamics in The Netherlands - Lourens Broersma; Jouke Van Dijk (European Regional Science Association (ERSA), 2001)
This paper analyses the response of the Dutch labour market to a regional labour demand shock. European-wide studies and US labour market studies found that in Europe adjustment to such a shock runs primarily through changes in participation, while in the US this is through migration of workers. Another striking difference is that the admustment process in the US takes places a much higher speed than in regions in European countries The main explanation for this phenomenon is the rigid labour market in Europe, against the flexible labour market in the US, which is expressed by the fact that spatial mobility among US workers is much higher than among European workers. A similar approach to the Dutch labour market shows that adjustment to labour demand shocks is primarily through changes in participation. In that sense it fits the European picture. As far as the speed of adjustment to a shock is concerned, the Dutch labour market seems more in line with American than with European levels. A disaggregate analysis shows that particularly the response of the northern labour market stands out. Adjustment to a shock is absorbed faster than in other Dutch regions. Furthermore, unemployment and migration are more important as absorption channels in the North than in the other regions.
Keywords: 330